The influence of blended learning model assisted by YouTube application during the Covid-19 pandemic on fifth graders’ thematic learning outcomes - Kharisma Nur Fitriyana; Khavisa Pranata (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2023)
The COVID-19 pandemic has forced educational institutions worldwide to rapidly adapt to remote teaching and learning methods. Blended learning models that combine online and offline methods have emerged as a popular approach to facilitate effective teaching during the pandemic. This study examines the influence of a blended learning model assisted by YouTube application on the thematic learning outcomes of fifth-grade students during the COVID-19 pandemic. The study uses a quasi-experimental design with a pre-test and post-test control group. The results show that the blended learning model significantly improved students' thematic learning outcomes compared to the traditional classroom approach. The study also found that the YouTube application played a significant role in facilitating students' engagement and motivation in the learning process. Overall, this study provides valuable insights into the effectiveness of blended learning models and the potential of technology-assisted learning during the COVID-19 pandemic.